2005
DOI: 10.1016/j.cell.2005.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Slug Antagonizes p53-Mediated Apoptosis of Hematopoietic Progenitors by Repressing puma

Abstract: In response to DNA damage, the p53 tumor suppressor can elicit either apoptosis or cell-cycle arrest and repair, but how this critical decision is made in specific cell types remains largely undefined. We investigated the mechanism by which the transcriptional repressor Slug specifically rescues hematopoietic progenitor cells from lethal doses of gamma radiation. We show that Slug is transcriptionally induced by p53 upon irradiation and then protects the damaged cell from apoptosis by directly repressing p53-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
269
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 362 publications
(294 citation statements)
references
References 39 publications
20
269
5
Order By: Relevance
“…These observations indicated that p53 does not require Snai2 to activate the cell cycle checkpoint by arresting in G1. Moreover, these results indicate Snai2 does not require p53 for its DNA damage protective function in MEFs in agreement with previous data in haematopoietic precursors Perez-Mancera et al, 2005;Wu et al, 2005). To confirm that our approach could be used to study the role of the p53-responsive Snai2 DNA damage-associated target genesgene Snai2 in DNA damage response, we next examined whether known target genes were modulated in control and Snai2-deficient MEFs after DNA doxorubicin treatment.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These observations indicated that p53 does not require Snai2 to activate the cell cycle checkpoint by arresting in G1. Moreover, these results indicate Snai2 does not require p53 for its DNA damage protective function in MEFs in agreement with previous data in haematopoietic precursors Perez-Mancera et al, 2005;Wu et al, 2005). To confirm that our approach could be used to study the role of the p53-responsive Snai2 DNA damage-associated target genesgene Snai2 in DNA damage response, we next examined whether known target genes were modulated in control and Snai2-deficient MEFs after DNA doxorubicin treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, constitutive activation of Snai2 could confer resistance properties to the tumour-target cells connecting DNA damage with the requirement of a critical level of Snai2 for cancer development. In agreement with these results, recently it has been shown Snai2 is a p53 target that antagonises p53-mediated apoptosis of haematopoietic progenitors (Wu et al, 2005). However, the effect of Snai2 on p53 target genes remains an open question (Haupt et al, 2006).…”
supporting
confidence: 55%
See 3 more Smart Citations